Implementation of smoke detector system in household kitchen based on HTTP protocol with DHT22 and MQ135 sensor integrated with WhatsApp chatbot - Aulia Desy Nur Utomo, Aulia Desy Nur Utomo; Feri Yasin; Muhammad Agung Nugroho (Institute of Computer Science (IOCS), 2025)
This research develops an Internet of Things (IoT)-based smoke detection system using MQ135 and DHT22 sensors integrated with WhatsApp chatbot via HTTP protocol. The system is designed to provide real-time notifications related to air quality, including gas concentration, temperature, and humidity. The test results show accurate and stable sensor performance in detecting environmental parameters. Evaluation is done through Quality of Service (QoS) analysis based on delay, jitter, packet loss, and throughput parameters. The test shows a fairly high network stability with 0% packet loss and an average throughput of 2045.53 Kbps, which falls into the Excellent and Good categories. However, the average delay of 2173.65 ms and jitter of 254.11 ms were classified as Poor, indicating the need for improvement in the responsiveness aspect. This research is expected to contribute to the integration of air quality monitoring systems with practical and easily accessible instant messaging services. The system offers an innovative solution for real-time smoke detection and early warning. Limitations of this study include limited data size and room for improvement in the interpretability and scalability of the system for wider IoT implementation.